A Close Assessment of X-ray Image Enhancement Techniques for Contraband Detection - Sajid Ullah, Khan; Wang, Yin Chai; Najeeb, Ullah; Engr., Abdul Rauf (IJCSIS, 2016)
X-ray image enhancement plays a vital role in the detection of explosive or illicit objects. X-ray image viewability is still a challenging task. To overcome this task, in this paper, we compare both new and old techniques of X-ray image enhancement for baggage inspection system on the basis of nine statistical measures of X-ray image viewability. From the experiments, it is concluded that some new techniques outclass the recent X-ray image enhancement methods that are regularly used at airports. From the viewability measurements, it is concluded that airport security baggage inspection system must be updated with our suggested enhancement approaches.